Improving Survey Response Rates from Parents in School-Based Research Using a Multi-Level Approach - Schilpzand, Elizabeth J. (PLoS One, 2015)
BACKGROUND: While schools can provide a comprehensive sampling frame for community-based studies of children and their families, recruitment is challenging. Multi-level approaches which engage multiple school stakeholders have been recommended but few studies have documented their effects. This paper compares the impact of a standard versus enhanced engagement approach on multiple indicators of recruitment: parent response rates, response times, reminders required and sample characteristics. METHODS: Parents and teachers were distributed a brief screening questionnaire as a first step for recruitment to a longitudinal study, with two cohorts recruited in consecutive years (cohort 1 2011, cohort 2 2012). For cohort 2, additional engagement strategies included the use of pre-notification postcards, improved study materials, and recruitment progress graphs provided to school staff. Chi-square and t-tests were used to examine cohort differences. RESULTS: Compared to cohort 1, a higher proportion of cohort 2 parents responded to the survey (76% versus 69%; p < 0.001), consented to participate (71% versus 56%; p < 0.001), agreed to teacher participation (90% versus 82%; p < 0.001) and agreed to follow-up contact (91% versus 80%; p < 0.001). Fewer cohort 2 parents required reminders (52% versus 63%; p < 0.001), and cohort 2 parents responded more promptly than cohort 1 parents (mean difference: 19.4 days, 95% CI: 18.0 to 20.9, p < 0.001). CONCLUSION: These results illustrate the value of investing in a relatively simple multi-level strategy to maximise parent response rates, and potentially reduce recruitment time and costs.